Workshop creating references on the final project of stikes hang tuah pekanbaru students using mendeley application - Yuda Irawan; Refni Wahyuni; Yulisman; Matthijs B Punt (Peneliti Teknologi Teknik Indonesia, 2021)
Making or compiling a final project report has many issues, one of which students frequently complain about: compiling a bibliography. The workshop aimed to provide students with knowledge about citing and compiling an automatic bibliography, as well as to take advantage of one of the advancements in information technology that students could use to compile a bibliography or reference by using an application. The workshop was held online using the Google Meet platform and the Mendeley application to create a list of references. The workshop activity went smoothly without any major impediments, and the participants were 44 Fifth Semester Diploma Midwifery students. Measurement of the introduction of the Mendeley application prior to the workshop using the evaluation questionnaire revealed that 95.45% of participants did not know the Mendeley application at all, while 4.55% knew about it. The result of the evaluation questionnaire found that 70.45% of participants said that the Mendeley application was easy to use, and 29.55% said that it was difficult to use. 100% of participants would use the Mendeley application to prepare the final assignment report (LTA).